The impact of firm strategy and foreign ownership on executive bonus compensation in Japanese firms - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2010)
Building on information-processing perspectives and the Japanese contextual factors, this study investigates the relationships between firm strategy and executive bonus pay as well as the moderating role of foreign ownership on the strategy–compensation relationship in Japanese firms. We focus on R&D investment and product diversification as strategy variables and investigate their direct effects on executive bonus pay. Further, we examine the moderating effects of foreign ownership on the strategy–pay sensitivity. The results, based on a sample of the 148 largest industrial firms in Japan for the 1990–1997 period, show that both R&D investment and product diversification are positively related to executive bonus pay. Our findings also indicate that foreign ownership negatively moderates the relationships between the strategy variables and executive compensation, suggesting that foreign investors play an active monitoring role, reducing cash bonus payments when their invested firms choose to increase R&D or pursue diversification strategy.